KOORDINASI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DENGAN KANTOR IMIGRASI DALAM PENDATAAN DOKUMEN KEIMIGRASIAN: Coordination between the Population and Civil Registration Service and the Immigration Office in the Data Collection of Immigration Documents - Najwa Fadhilah; Tri Sulistyowati (Reformasi Hukum Trisakti, 2026)
The collection of immigration documents requires accurate and consistent population data, as these documents are issued based on the identities of residents managed by the Population and Civil Registration Office (Disdukcapil). This institution also requires cooperation with the immigration office. The research question is: how does the Population and Civil Registration Agency coordinate the data collection for immigration documents? This study uses a normative juridical method, is descriptive in nature, relies on secondary data, employs qualitative data analysis, and draws deductive conclusions. The results of the discussion and conclusions show that inter-agency coordination is influenced by differences in authority, institutional structure, and the administrative systems used by each agency. Disdukcapil plays a strategic role in ensuring the quality of population data, while the immigration office utilises this data in the process of data collection and issuance of immigration documents. Coordination constraints arise due to limited system integration and differences in work procedures. Strengthening coordination requires clarity in the regulation of population data utilisation, harmonisation of procedures, and support from an integrated administrative system so that immigration document data collection can run effectively and accurately.